A Simulation of the Gypsum Content Distribution North of Baghdad - Abdulwadood, Huda W.; Hameed, Reem Sh.; Abdul_Hammed, Abeer N. (Iraqi Journal of Science, 2026)
Due to its high solubility and unpredictable behavior, gypsum content is significantly challenging in engineering tests and agriculture processes. Another crucial element is that it causes long-term groundwater pollution and impacts buildings. This study explores the distribution and characteristics of gypsum soil in Salah Al-Din Governorate, Iraq, integrating field sampling, remote sensing techniques, and GIS tools. The land cover of the research area (27,751 km2) was classified into four types: 15% bar soil, 40% structures, 16% vegetation and agricultural fields, and 8% water bodies. Gypsum content was measured using the Al-Mufty approach, while reflectance indices interpolation techniques, such as the Bar Soil Index (BSI) and the inverse distance weighted, were applied to map the distribution of gypsum. The results revealed gypsum concentrations ranging between 12.9% and 68.75% with associated SO3 levels of 6.13% to 32.73%. Flat, low-lying areas exhibited higher gypsum and SO3 concentrations, with spectral reflectance values of 0.01-0.5, aligning with the United States Geological Survey standards. Elevation models showed gypsum distribution primarily between 53 and 248 m above sea level. Slope and aspects analyses indicated gypsum presence in regions prone to water evaporation and distant from groundwater. Reducing on-site engineering testing by adding GIS and remote sensing tools to complement field engineering work contributes to reducing the use of equipment and transportation services and lowering time, cost, and efforts, significantly enhancing sustainable development. This study bridges a research gap in exploring the distribution of gypsum soils and associated technical and environmental challenges by integrating engineering tests with geographical information systems and remote sensing indicators. This enriches the literature, informs decision-making, and promotes sustainable development.